La eficaz gestión y control de la cooperación técnica internacional en el desarrollo nacional del perú - Polanco Mantilla, Yovani Isabel (2009)
The present thesis to opt for the title of lawyer, is oriented to carry out a systematic study, of how the International Technical Cooperation is managed and controlled so that it can be effective to the extent that the sectors most in need reach. Thus, in order to give a doctrinal and normative scope and verify if in practice it has been effected, this thesis has been developed in the following Parties. In the first part the Methodological Framework framed in the antecedents of International Cooperation is developed as well as the approach of the problem of the present thesis, its motivation and justification of the same, the hypothesis of both the general and secondary hypothesis the analysis of its variables and Their indicators. In the second part we have the Normative Theoretical Framework of International Technical Cooperation developed in eight chapters; With the thematic dispersion of the role of the State and the Society for a prospective of International Cooperation, its organization and strategies for effective participation, International Technical Cooperation itself, conceptual framework and its modalities, reasons for cooperation, The industrialized countries, the recipient countries. International Technical Cooperation as a foreign policy instrument and objective; Efficiency and effectiveness for a prospect of international technical cooperation. The third part is the development of the research, consisting of the result of the interview and the survey carried out, as well as the discussion thereof; Including an analysis, testing and verification of the objectives and assumptions. The fourth part is the special chapter, the practical case is developed that has as scenery the city of Pisco, and the earthquake that nitrogen to that city, that as a consequence of the poor management in the channeling of the international aid, the crime was configured Of peculation. Finally, it establishes the pertinent conclusions and recommendations, which must be taken into consideration for an effective and effective International Cooperation in the national development of Peru